Elektroniczny system obiegu dokumentów jako instrument wspomagający proces decyzyjny w instytucjach publicznych - Kalisiak-Mędelska, Magdalena (Electronic document management as support for process of decision-making in public sector, 2006)
This article describes selected problems connected with the modernization of public administration. It focuses on technologic changes occuring in the process of supplying data. Presently, it is standard to provide public services with the help of advanced information technology. Electronic Dokument Management is the instrument which supports this process in many areas such as efficiency or quality. Although it has many advantages its high cost very often prevents local authorities from implementing it. It concerns especially small cities and their governments.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 408-416